Evolution of the human diet : the known, the unknown, and the unknowable - Ungar, Peter S. (Human evolution series., 2007)
I. Introduction. 1. Early Hominin Diets: Overview and Historical Perspectives, Alan Walker. 2. Whose Diet? An Introduction to the Hominin Fossil Record, Amanda G. Henry and Bernard Wood. II. The Hominin Fossil Record. 3. The Evolution of the Hominin Diet from a Dental Functional Perspective, Peter W. Lucas. 4. Dental Functional Morphology: The Known, the Unknown, and the Unknowable, Peter S. Unger. 5. What Do We Know and Not Know about Diet and Enamel Structure, Mark F. Teaford. 6. Mandibular Biomechanics and the Paleontolgical Evidence for the Evolution of Human Diet, David J. Daegling and Fr.